First record of the leafhopper genus Soractellus Evans, 1966 (Hemiptera: Cicadellidae: Deltocephalinae) from China, with description of a new species - Xing, Ji-Chun; Li, Zi-Zhong (Zootaxa, 2014)
The genus Soractellus Evans, 1966 is reported for the first time based on a new species, Soractellus jianfengensis sp. nov., here described and illustrated from China. A key is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).